GAMBARAN FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPERTENSI PADA AKSEPTOR KONTRASEPSI PIL (Studi di Wilayah Kerja Puskesmas Kuwarasan Kabupaten Kebumen) - Umi Ardiningsih; Lintang Dian Saraswati; Mateus Sakundarno Adi; Ari Udiyono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Hypertension in woman tends to be higher than in man. One of them is the use of the hormonal contraceptive tool such as oral contraceptive. The purpose of this research is to figure the factor which is related to the occurrence of hypertension in woman oral contraception acceptor at Public Health Center of Kuwarasan, Kebumen regency.This research is a descriptive study with cross-sectional approach. The samples of this research included 100 women of fertile couples which are selected randomly and conducted the interview, filing questionnaires, and measurement. Data show that mostly respondents experience hypertension at age more than 35 years old (57,7%); have history of family hypertension (58,6%); status of obesity (59,6%); low physical activity (56,4%); high atrium consumption (70%); and too heavy stress level (100%). Need to increase awareness to maintain a healthy lifestyle by the acceptor and the socialization of the government regarding contraceptives to the public.